Pendampingan Mahasiswa dalam Pelaksanaan Kegiatan Magang di SMA Darul Falah - Siti Mastiyah (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2025)
Internships are field practice activities that must be undertaken by students of the Undergraduate Program in Islamic Education before completing their final thesis. Through internship programs, students have the opportunity to gain direct experience in real working environments while applying various theories acquired during their academic studies. Student mentoring in the implementation of internship activities at SMA Darul Falah aims to bridge the theoretical learning obtained at the university with professional practice in the field. This community service activity was conducted over a period of two months, from August 22 to October 23, 2025, and involved 12 students from the Islamic Education Study Program. The internship activities were carried out using a classroom teaching practice method. The results of the student mentoring activities included internship preparation, student placement, monitoring of internship implementation, student withdrawal, and the preparation of internship activity reports.